2021
DOI: 10.1038/s41598-020-80412-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics analysis of postoperative delirium

Abstract: Postoperative delirium is the most common complication among older adults undergoing major surgery. The pathophysiology of delirium is poorly understood, and no blood-based, predictive markers are available. We characterized the plasma metabolome of 52 delirium cases and 52 matched controls from the Successful Aging after Elective Surgery (SAGES) cohort (N = 560) of patients ≥ 70 years old without dementia undergoing scheduled major non-cardiac surgery. We applied targeted mass spectrometry with internal stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 83 publications
3
28
0
1
Order By: Relevance
“…In the Successful Aging after Elective Surgery (SAGES) study of 566 over 70-year-old patients undergoing major non-cardiac surgery in the US, POD defined by a combination of CAM and chart review occurred in 24% of patients. Self-reported education was not associated with POD risk (Cavallari et al 2016(Cavallari et al , 2017Cizginer et al 2017;Hshiesh et al 2017;Inouye et al 2016;Tripp et al 2021;Vasunilashorn et al 2017). Another large study, the PAWEL study based in Germany (Deeken et al 2022), as well as smaller cohort studies from Europe, Asia, and South America support these null results (Jiang et al 2017;Kazmierski et al 2013;Mahanna-Gabrielli et al 2020;Puustinen et al 2016;Ristescu et al 2021;Sauer et al 2017;Seo et al 2014;Xue et al 2016), whereas other investigations do suggest a low education as a risk factor for POD (Dworkin et al 2016;Gu et al 2021;Guan et al 2021;Huang et al 2021;Ma et al 2021;McAlpine et al 2008;Ordóñez-Velasco and Hernández-Leiva 2021;Schoen et al 2011;Sprung et al 2017;Su et al 2019;Tenpaku et al 2021;Tobar et al 2018).…”
Section: Education and Podmentioning
confidence: 94%
“…In the Successful Aging after Elective Surgery (SAGES) study of 566 over 70-year-old patients undergoing major non-cardiac surgery in the US, POD defined by a combination of CAM and chart review occurred in 24% of patients. Self-reported education was not associated with POD risk (Cavallari et al 2016(Cavallari et al , 2017Cizginer et al 2017;Hshiesh et al 2017;Inouye et al 2016;Tripp et al 2021;Vasunilashorn et al 2017). Another large study, the PAWEL study based in Germany (Deeken et al 2022), as well as smaller cohort studies from Europe, Asia, and South America support these null results (Jiang et al 2017;Kazmierski et al 2013;Mahanna-Gabrielli et al 2020;Puustinen et al 2016;Ristescu et al 2021;Sauer et al 2017;Seo et al 2014;Xue et al 2016), whereas other investigations do suggest a low education as a risk factor for POD (Dworkin et al 2016;Gu et al 2021;Guan et al 2021;Huang et al 2021;Ma et al 2021;McAlpine et al 2008;Ordóñez-Velasco and Hernández-Leiva 2021;Schoen et al 2011;Sprung et al 2017;Su et al 2019;Tenpaku et al 2021;Tobar et al 2018).…”
Section: Education and Podmentioning
confidence: 94%
“…These age-related postoperative complications affect the health care system and socioeconomic development with the rapid growth of the aging population worldwide [ 2 ]. More studies have shown that neuroinflammation is one of the pathophysiological mechanisms of cognitive dysfunction in elderly rodents after anesthesia and surgery [ 3 , 4 ]. However, how neuroinflammation attacks the elderly brain after anesthesia and surgery remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…1-4, It is identified by clinical diagnosis, and there is no laboratory test or any diagnostic kit available that can help in its diagnosis. 5,6 Delirium is frequently observed in older patients who are hospitalized and is associated missed or delayed diagnosis resulting in extended length of hospitalization, development of complications with decline in physical and cognitive function, loss of independence, and increased morbidity and mortality. [2][3][4]6 With the exponential increase in the population of older adults globally, delirium prevention has become extremely pertinent.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 In US, more than 2.6 million older adults (>65 years) develop delirium each year and cost the healthcare industry approximately $164 billion. 5 , 8 There are different delirium prevention programs initiated by multiple organizations to apprise people about the subject. Despite growing awareness, there is insufficient knowledge among older adults and inadequate education and training of students and health-care professionals on the topic of delirium.…”
Section: Introductionmentioning
confidence: 99%